Effect of Stress on job satisfaction among nurses in central kerala - Neenu Ann Mathew (IOSR Journal of Business and Management (IOSR-JBM), 2013)
Modern life is full of stress. Nursing is, by its very nature, an occupation subject to a high degree of stress. This profession involves working with people who are themselves suffering a considerable degree of stress. The purpose of this paper is to examine job stress and its impact on the job satisfaction among nurses in private hospitals. The survey based instrument was used to gather the responses from the nurses working in leading hospitals having more than 407 beds situated in Central Kerala. Questionnaire was the main tool used to collect the pertinent data from the selected sample respondents. 100 respondents participated in this survey. This study is limited to hospitals .The results may not be applicable to other business organization. The study has been analyzed through simple percentage method and SPSS.